Defaunation and forest degradation in Central African logging concessions: how to measure the impacts of bush meat hunting on the ecosystem? case studies on measuring and assessing forest degradation - Nasi, Robert; Vliet, N. van (Food and Agriculture Organization of the United Nations, 2009)
The present paper is a review of the methods used for assessing defaunation, as a forest degradation component, linked to logging and logging concessions with an emphasis on mammals and Central Africa Rainforests. A discussion on the usefulness and weaknesses of these methods is provided